Presupuesto de la región Loreto y su relación con el gasto público en inversión, periodo 2019-2023 - Garcia Gonzales, Paula Daniela (2025)
The importance of the regional public budget lies in the fact that it is essential for the development and well-being of the Loretana population, due to the way in which it allocates the necessary financial resources. That is why this research aims to identify the relationship between the budget of the Loreto region and public spending on investment, period 2019 - 2023, with a quantitative study approach of descriptive - non-experimental correlational design. The results reveal that a level of statistical significance is not reached, which suggests that although the increase in the budget has been constant, there is no significant direct relationship with investment spending. The study concludes that the Loreto region has experienced an improvement in resource allocation, especially in non-financial assets, but recommends strengthening budget planning and monitoring of investment projects to improve efficiency and maximize long-term benefits.